2011
DOI: 10.3791/2938
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-Mediated Virus-Induced Gene Silencing Assay In Cotton

Abstract: Cotton (Gossypium hirsutum) is one of the most important crops worldwide. Considerable efforts have been made on molecular breeding of new varieties. The large-scale gene functional analysis in cotton has been lagged behind most of the modern plant species, likely due to its large size of genome, gene duplication and polyploidy, long growth cycle and recalcitrance to genetic transformation 1 . To facilitate high throughput functional genetic/genomic study in cotton, we attempt to develop rapid and efficient tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 8 publications
1
84
0
1
Order By: Relevance
“…Because cotton transformation is laborious and technically challenging, the development of a rapid method for gene functional analysis would greatly extend the power of molecular analysis. Gao et al (2011aGao et al ( , 2011b have shown that TRV-VIGS functions in cotton leaves with a 100% silencing efficiency. Extending the utility of this method, we showed here that sTRV-VIGS can also be effective in suppressing gene expression in reproductive organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because cotton transformation is laborious and technically challenging, the development of a rapid method for gene functional analysis would greatly extend the power of molecular analysis. Gao et al (2011aGao et al ( , 2011b have shown that TRV-VIGS functions in cotton leaves with a 100% silencing efficiency. Extending the utility of this method, we showed here that sTRV-VIGS can also be effective in suppressing gene expression in reproductive organs.…”
Section: Discussionmentioning
confidence: 99%
“…Our method for agroinfection of cotton plants was different from that of Gao et al (2011aGao et al ( , 2011b, who used a syringe to infiltrate Agrobacterium tumefaciens culture into two fully expanded cotyledons. By contrast, we used cotton plants with two to four true leaves, vacuum infiltrated the leaves with A. tumefaciens culture, and subsequently drenched the root system using the same culture.…”
Section: Synthetic Trv-induced Silencing Of Proanthocyanidin Biosynthmentioning
confidence: 99%
See 1 more Smart Citation
“…The VIGS transient expression methods followed Gao et al (2011). VIGS-infiltrated seedlings were allowed to grow for 2 wk until the two-true-leaf stage and then leaves were collected and stored at −80°.…”
Section: Methodsmentioning
confidence: 99%
“…Tuttle et al [15] reported the silencing of two visible marker genes, magnesium chelatase subunit I and phytoene desaturase ( PDS ), using the geminivirus Cotton leaf crumple virus (CLCrV) as a vector. Gao et al [16,17] used the Tobacco rattle virus (TRV) as a vector to silence another marker gene, cloroplastos alterados 1 ( CLA1 ). Although both VIGS systems were shown to work in G.…”
Section: Introductionmentioning
confidence: 99%